2021
DOI: 10.3389/fpsyt.2021.653662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronavirus Disease 2019 on the Psychology and Behavior of Patients on Methadone Maintenance Treatment in Wuhan, China: A Clinical Observational Study

Abstract: Methadone maintenance treatment (MMT) is a national strategy adopted for the treatment of heroin dependency in China. The sudden outbreak of coronavirus disease 2019 (COVID-19) and the resultant social isolation in Wuhan have also had a significant negative impact on local patients undertaking MMT. In this study, 76 patients on MMT from the Wuhan First Health Clinic were selected as the research objects to investigate the effect of COVID-19 on the levels of stress, anxiety, and depression, as well as the withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Another drug identified was sertraline, which is used to treat depression [ 60 ]. Anxiety and depressive symptoms increase during the COVID-19 outbreak [ 61 ]. Studies have shown that in vitro stimulation with 8-bromo-cAMP activates the cAMP/PKA pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another drug identified was sertraline, which is used to treat depression [ 60 ]. Anxiety and depressive symptoms increase during the COVID-19 outbreak [ 61 ]. Studies have shown that in vitro stimulation with 8-bromo-cAMP activates the cAMP/PKA pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 and the subsequent social isolation have triggered NA such as stress, depression, and anxiety, which increased the cravings and consumption of addictive drugs. Therefore, during the severe period of the pandemic, it is necessary to provide psychological counseling for elderly patients with SUDs, proactively treat their NA, and improve drug management after the pandemic to prevent drug (legal or illegal) abuse ( 22 ). In addition, taking a break from the news and social media can indirectly help treatment and prevent relapse ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, for the elderlies with substance use disorders (SUDs), it is obvious that their mental and psychological problems are rarely considered by clinicians and researchers before their physical symptoms are addressed. However, studies have shown that the mental and psychological problems of patients with SUDs might relapse or be exacerbated by social isolation and lockdown during a pandemic (20)(21)(22). Patients with previous SUDs are at greater risk of adverse consequences after contracting COVID-19 (23).…”
Section: Introductionmentioning
confidence: 99%
“…Another study found an increase in 147 healthy adult controls, but not 345 adults with bipolar disorder (Yocum et al, 2021). Two smaller studies also found an increase in anxiety; the first in 76 Chinese participants receiving methadone maintenance treatment for substance use disorder (Liu et al, 2021); and the next in 46 American older adults with PTSD, but not 30 traumaexposed older adults without PTSD (Rutherford et al, 2021). A third study found no change in a sample of 35 adults with autism spectrum disorder in Spain (Lugo-MarĂ­n et al, 2021).…”
Section: Anxiety (K = 47)mentioning
confidence: 97%